Challenges for donor agency country-level performance assessment: a review - Ireland, Mark; Saltmarshe, Douglas; McGregor, J. Allister (2003)
This review of country-level performance assessment in donor agencies is primarily based upon the experiences documented by bilateral donors to developing countries. The review suggests that four emerging themes can be identified in the literature on country-level performance review: ownership, decentralisation and leadership, accountability and learning and complexity. The review considers the implementation of `results-based' approaches used by a number of international agencies and examines their relationship with `evidence-based' approaches. A key challenge, in the development of performance assessment, is bringing in a stronger evidence-based approach into the planning and evaluation of donor country-level programmes. - Reproduced.
Keywords: Performance appraisal; Foreign aid